2021
DOI: 10.1177/2049936121998562
|View full text |Cite
|
Sign up to set email alerts
|

Personal protective equipment use by healthcare workers in intensive care unit during the early phase of COVID-19 pandemic in Italy: a secondary analysis of the PPE-SAFE survey

Abstract: Background: Italy was the first Western country to be heavily affected by COVID-19. Healthcare workers (HCWs) were exposed to a high risk of occupational infection, partially due to insufficient personal protective equipment (PPE) supplies. This study aimed to describe the practices, availability, training, confidence in PPE use and the adverse effects due to extended PPE use, as reported by HCWs in Italy. We also aimed to provide a comparison between Italian data and those from other countries. Methods: This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 16 publications
2
35
0
Order By: Relevance
“…On the other hand, the ICUs may have been overcrowded in the period of peak of COVID-19 pandemic, with a possibly inadequate staffing (e.g., nurse to patient ratio) and more episodes of cross-contaminations. Healthcare workers may have also encountered difficulties related to the wearing of personal protective equipment in the setting of COVID-19-dedicated ICUs [38]. When considered together, these issues may have reduced the adherence to infection control standard and VAP prevention bundles [16].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the ICUs may have been overcrowded in the period of peak of COVID-19 pandemic, with a possibly inadequate staffing (e.g., nurse to patient ratio) and more episodes of cross-contaminations. Healthcare workers may have also encountered difficulties related to the wearing of personal protective equipment in the setting of COVID-19-dedicated ICUs [38]. When considered together, these issues may have reduced the adherence to infection control standard and VAP prevention bundles [16].…”
Section: Discussionmentioning
confidence: 99%
“…Japanese respondents who reported significant thirst were 32.2%, while 47.4% of worldwide respondents reported this issue. Additionally, a recently published secondary analysis of the PPE-SAFE study in Italy (Ippolito et al, 2021) reported that the median time of wearing PPE continuously was 5 h (Interquartile range: 4-6 h). This finding was statistically significantly higher than other countries.…”
Section: Discussionmentioning
confidence: 99%
“…This scenario may even more be exacerbated in Italy during the first wave, in light of the restrictive measures which were applied to avoid the collapse of the national health system in front of the devastating and unexpected spreading of COVID-19 [ 26 ]. Uncontrollable epidemic spreading induced Italian Government to declare a nationwide lockdown and to release indication for mandatory utilize of personal protective equipment/individual protection devices (PPE/DPI) [ 27 ]. On the other hand, prolonged wearing of face and hand covering tools might have affected bleeding frequency of nasal, oral, and skin telangiectases in HHT patients.…”
Section: Introductionmentioning
confidence: 99%